Methods of Activation of Students‘ Cognitive Activity (Journal of Educational Sciences, 2022)
The formation of the cognitive activity of schoolchildren in the modern education system is one ofthe most urgent problems of pedagogical science and practice. Activity is an active state of depictingand changing reality, which plays a leading role in the development of a person, the formation of hispersonality. It is important that the teacher uses an effective method in the process of acquiring knowledge, skills of students.The purpose of this study is to theoretically substantiate the possibility of developing the cognitiveactivity of 7th grade students in the learning process and to determine the influence of the methods suchas «Bloom’s Cube», «STEAM», «GBL» and «Agrolab» on the development of students’ cognitive activity.This study was carried out on the basis of an empirical method at the Nazarbayev IntellectualSchool of Chemistry and Biology in Turkestan. In the practical part of the study, it was studied how thechosen methods influence the development of students’ cognitive activity. To determine the level ofknowledge of students, the methods “diagnostics of short-term auditory memory”, “comparison of concepts”, “drawing figures by O.M. Dyachenko. In the course of the study, the level of cognitive activityof students was diagnosed twice. Comparing the results of the study, it was found that the methods of“Bloom’s Cube”, “STEAM”, “GBL” and the “Agrolab” contributed to an increase in the level of cognitiveactivity of students.Key words: cognitive activity, «Bloom’s Cube» method, «STEAM», «GBL».